Sociolinguistic Issues in CSOL Testing - Udier, Sanda Lucija; Čilaš Mikulić, Marica (2008)
The aim of presentation was to show sociolinguistic and extralinguistic issues on CSOL assessment and testing. It showed Croatian legislation on it, glotodidactical and organisational matters and needs in the future.
Projekt MZOS
ENG